2007
DOI: 10.1002/hup.845
|View full text |Cite
|
Sign up to set email alerts
|

An open‐label study of quetiapine in anorexia nervosa

Abstract: A double-blind placebo controlled study is required to further evaluate the therapeutic utility of quetiapine in severely ill AN patients beyond multidisciplinary specialist intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
0
24
0
1
Order By: Relevance
“…Cheer and Wagstaff, 2004;Harvey et al, 2006;Keefe et al, 1999;Voruganti et al 2007). Preliminary data suggest that quetiapine might improve neurocognition in anorexia nervosa (Bosanac et al, 2007) and -as an add-on to an antidepressant -it does not negatively impact on cognition in obsessive compulsive disorder (de Geus et al, 2007). In the latter study, only failure to maintain set on the Wisconsin Card Sorting Test was reported to be associated with quetiapine administration.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Cheer and Wagstaff, 2004;Harvey et al, 2006;Keefe et al, 1999;Voruganti et al 2007). Preliminary data suggest that quetiapine might improve neurocognition in anorexia nervosa (Bosanac et al, 2007) and -as an add-on to an antidepressant -it does not negatively impact on cognition in obsessive compulsive disorder (de Geus et al, 2007). In the latter study, only failure to maintain set on the Wisconsin Card Sorting Test was reported to be associated with quetiapine administration.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast to BPD, research in other psychiatric disorders has applied neurocognitive performance as a method to evaluate efficacy in treatment studies in schizophrenia (e.g. Harvey et al, 2006), obsessive-compulsive disorder (de Geus et al, 2007) and anorexia nervosa (Bosanac et al, 2007). Although participant characteristics such as motivation may have an effect on task performance, neurocognitive assessment is not subject to the personal interpretation of statements or phrases in questionnaires and interviewer-rated measures.…”
Section: Introductionmentioning
confidence: 98%
“…The overall quality of the evidence examined was poor-four studies were deemed Category A (a RCT as a part of a high quality and consistent body of literature) (Bissada, Tasca, Barber, & Bradwejn, 2008;Brambilla et al, 2007a;Mondraty, Birmingham, Touyz, Sundakov, Chapman, & Beumont, 2005;National Institute of Clinical Excellence, 2005;Ruggiero, Laini, Mauri, Ferrari, Clemente, Lugo, Mantero, Redaelli, Zappulli, & Cavagnini, 2001), the majority of openlabel studies as Category B (well conducted clinical trials without randomization) (Barbarich et al, 2004;Bosanac et al, 2007;Fernandez, Ductor, Galan, & Martinez, 2006;Powers, Bannon, Eubanks, & McCormick, 2007;Powers, Santana, & Bannon, 2002) and the rest as Category C (clinical experience from respected authorities, mainly case reports).…”
Section: Methodsmentioning
confidence: 99%
“…One of the few trials of quetiapine is an open-label study of eight adult patients hospitalized in a specialist eating disorders inpatient unit (Bosanac et al, 2007). An average dose of 520 mg/day was used over 8 weeks, with no serious side effects experienced.…”
Section: Open-label Trials Of Quetiapinementioning
confidence: 99%
“…Adverse events included dizziness, muscle pain, lightheadedness, sleepiness, paesthesias and headache, each complaint was considered mild and not necessarily attributable to the medication, but possibly related to cachexia. Another 8-week open trial with quetiapine (average daily dose during 1st month: 282 mg, during whole 8 weeks: 520 mg/day) including 8 females with anorexia nervosa (average age 33.25 years, average duration of disease: 14 years) revealed statistically significant improvements of anorexia symptoms (Eating Disorder Examination12th Edition, EDE-12), whereas obsessive-compulsive and depressive symptoms (Yale-Brown ObsessiveCompulsive Scale, Y-BOCS; Montgomery-Asperg Scale, MADRS) as well as anorexic delusional beliefs about weight, eating and shape (delusions subscale of the Scale for the Assessment of Positive Symptoms, SAPS) after 4 weeks only showed a trend towards improvement (Bosanac et al, 2007).…”
Section: Applicability Of Atypical Antipsychotics In Anorexia Nervosamentioning
confidence: 93%